A genetic study regarding the number of grains in spike in winter wheat - Bunta, Gheorghe; Bucurean, Elena (Acta Agraria Debreceniensis, 2010)
Grain number per spike was studed in 6 winter wheat varieties and all their 30 direct and reciprocal F1 hybrids. Parentsincluded 4 released Romanian variety, the old american Atlas 66 and a dwarf breeding line, Oradea 79. This line has a low number ofgrains/spike, but is important in breeding program for here reduced height. General and specific combining abilities were computed andgenetic effects were estimated using Griffing’s method 1, model 1, as modified by Cabulea (1983).For this diallel crosses, gene interactions and the interaction between cytoplasm and nuclear genes were highly significant andthe ratio of additive and non-additive effects was close to one.The variety Fundulea 29 showed the highest general combining ability and it is recommended as a good parent for increasinggrain number/spike. Mid-parent heterosis was significant in 9 out of the 30 cases, mostly in hybrids involving the breeding line Oradea 79.In 3 cases the number of grains/spike of F1 hybrids was significantly lower than the average of the parents. The breeding line Oradea 79 hada significant negative general combining ability, but showed significant positive specific combining ability in most crosses, as well as asignificant positive effect of its cytoplasm. These results are considered to indicate that there are chances of improving the grainnumber/spike in some crosses with Oradea 79.